Violence exposure is associated with preference for masculine faces: evidence from Senegal - Tureček, Petr; Černý, Viktor; Diallo, Mame Yoro; Cissé, Ngoné; Pokorný, Šimon; Kleisner, Karel (Proceedings. Biological sciences, 2025)
It has been suggested that in threatening environments, both women and men should prefer more masculine men as romantic and coalition partners, respectively. Empirical evidence for this hypothesis has been weak or inconsistent, primarily because most experimental research has focused on elevating the perceived danger from other men through virtual threats. This study investigates whether personal experience with violence predicts the preference for masculine features in 326 Senegalese participants presented with pairs of manipulated facial photographs of West African men (one more feminine, one more masculine) and asked to indicate which face is more attractive (to women) or more trustworthy (to men). The findings reveal a strong association between violence exposure and facial feature preferences. Those who experienced (particularly physical) violence showed a higher preference for masculinized faces (up to 95% in women, 82% in men) compared to the baseline (57% in women, 63% in men). This difference is proposed to reflect an adaptive strategy of prioritizing physical protection in settings with a higher incidence of violent confrontations. Much of the variance can be found between groups. The direct effect of experienced violence diminishes over time, which suggests a dynamic interplay between innate predispositions and environmental influences on aesthetic preferences.
Keywords: facial masculinity; Humans; attractiveness; violence exposure; Exposure to Violence; evolutionary psychology; obličej; Female; mladý dospělý; dospělí; contextual preferences; lidé; trustworthiness; mužskost; Adult; vystavení násilí; ženské pohlaví; Male; Adolescent; Senegal; Young Adult; Masculinity; Face; mužské pohlaví; mladiství